2015
DOI: 10.1038/ncomms9300
|View full text |Cite
|
Sign up to set email alerts
|

Transgranular liquation cracking of grains in the semi-solid state

Abstract: Grain refinement via semi-solid deformation is desired to obtain superior mechanical properties of cast components. Using quantitative in situ synchrotron X-ray tomographic microscopy, we show an additional mechanism for the reduction of grain size, via liquation assisted transgranular cracking of semi-solid globular microstructures. Here we perform localized indentation of Al-15wt.%Cu globular microstructures, with an average grain size of ∼480 μm, at 555 °C (74% solid fraction). Although transgranular fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 53 publications
2
55
0
Order By: Relevance
“…In situ radiography [Lee and Hunt, 1997] and synchrotron X-ray tomography (sCT) have become key tools and are now regularly used to quantify crack and other defect formation in a wide range of fields. These include metallic alloy micromechanics to granular flow and even the cracking of high-temperature semisolid metals [Kareh et al, 2014;Karagadde et al, 2015]. They have also been used in a number of geological applications, such as observing the influence of fabric in soils to shear band formation [Fonseca et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…In situ radiography [Lee and Hunt, 1997] and synchrotron X-ray tomography (sCT) have become key tools and are now regularly used to quantify crack and other defect formation in a wide range of fields. These include metallic alloy micromechanics to granular flow and even the cracking of high-temperature semisolid metals [Kareh et al, 2014;Karagadde et al, 2015]. They have also been used in a number of geological applications, such as observing the influence of fabric in soils to shear band formation [Fonseca et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, synchrotron X-ray imaging has been extensively applied to the in situ study of solidification [2,11,12], fragmentation [8,13] and coarsening mechanisms [14], pore and bubble growth during solidification [15,16], and semi-solid processing [17][18][19]. Huang et al [20] recently reported measurement of the size distribution of cavitation gas bubbles in an AlCu alloy melt using the synchrotron X-ray radiography whilst the current authors used it to study the ultrasonic capillary effect in a molten metallic alloy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently Kareh et al 30. Karagadde et al 31. utilised time-resolved tomography to reveal rotation and transgranular liquation during semi-solid processing.…”
mentioning
confidence: 99%